Malaria parasites in macaques in Thailand: stump-tailed macaques (Macaca arctoides) are new natural hosts for Plasmodium knowlesi, Plasmodium inui, Plasmodium coatneyi and Plasmodium fieldi - Wirasak Fungfuang; Chanya Udom; Daraka Tongthainan; Khamisah Abdul Kadir; Balbir Singh (Malaria Journal, 2020)
Abstract Background Certain species of macaques are natural hosts of Plasmodium knowlesi and Plasmodium cynomolgi, which can both cause malaria in humans, and Plasmodium inui, which can be experimentally transmitted to humans. A significant number of zoonotic malaria cases have been reported in humans throughout Southeast Asia, including Thailand. There have been only two studies undertaken in Thailand to identify malaria parasites in non-human primates in 6 provinces. The objective of this study was to determine the prevalence of P. knowlesi, P. cynomolgi, P. inui, Plasmodium coatneyi and Plasmodium fieldi in non-human primates from 4 new locations in Thailand. Methods A total of 93 blood samples from Macaca fascicularis, Macaca leonina and Macaca arctoides were collected from four locations in Thailand: 32 were captive M. fascicularis from Chachoengsao Province (CHA), 4 were wild M. fascicularis from Ranong Province (RAN), 32 were wild M. arctoides from Prachuap Kiri Khan Province (PRA), and 25 were wild M. leonina from Nakornratchasima Province (NAK). DNA was extracted from these samples and analysed by nested PCR assays to detect Plasmodium, and subsequently to detect P. knowlesi, P. coatneyi, P. cynomolgi, P. inui and P. fieldi. Results Twenty-seven of the 93 (29%) samples were Plasmodium-positive by nested PCR assays. Among wild macaques, all 4 M. fascicularis at RAN were infected with malaria parasites followed by 50% of 32 M. arctoides at PRA and 20% of 25 M. leonina at NAK. Only 2 (6.3%) of the 32 captive M. fascicularis at CHA were malaria-positive. All 5 species of Plasmodium were detected and 16 (59.3%) of the 27 macaques had single infections, 9 had double and 2 had triple infections. The composition of Plasmodium species in macaques at each sampling site was different. Macaca arctoides from PRA were infected with P. knowlesi, P. coatneyi, P. cynomolgi, P. inui and P. fieldi. Conclusions The prevalence and species of Plasmodium varied among the wild and captive macaques, and between macaques at 4 sampling sites in Thailand. Macaca arctoides is a new natural host for P. knowlesi, P. inui, P. coatneyi and P. fieldi.